Improvements in Soil C and N Compositions After 40 and 80 Years of Reforestation in Subtropical Low Mountain Forests. Issue 9 (10th September 2020) - Shiau, Yo‐Jin; Chang, Ed‐Haun; Tian, Guanglong; Chen, Tsai‐Huei; Chiu, Chih‐Yu
Abstract: Reforestation is an important step toward recovering soil quality and wildlife habitats that are degraded due to deforestation. However, little is known about how soil C and N compositions in subtropical forests evolve after decades of reforestation. This study comprehensively evaluated the differences in soil C and N fractions in 40‐ and 80‐year‐old secondary (reforested) coniferous forests and a natural broadleaf forest. Although reforestation with coniferous plants appeared to increase soil organic matter and labile C levels, the ratio of soil labile C to total organic C was lower in the reforested coniferous forests than the natural broadleaf one. The trend in the labile N to total N ratio as coniferous reforestation progresses follows that of C. Furthermore, the percentage of recalcitrant C as total soil organic C was higher in the reforested coniferous forests than the natural broadleaf one. This feature of C composition in reforested coniferous forest causes environmental stress to microbes (as indicated by a high metabolic quotient) in the forest, even several decades after reforestation of a former broadleaf forest site. Results from this study demonstrate that it takes a very long time for reforestation with coniferous vegetation to restore the soil chemical properties of the previous natural forest. Key Points: Reforestation with conifers favored soil C and N buildup but decreased the soil labile C to total organic C ratio Microbial communities can still experience environmental stress from decomposition‐resistant coniferous litter, as evident from high q CO2, even after decades of reforestation